DNA Barcoding in Hibiscus rosa-sinenensis Variants using matK and trnH--psbA Barcodes - Marcella, Meia Garry Enchangan (2017)
Hibiscus rosa-sinensis is a versatile plant species of many uses ranging from medicinal to a food source and even industrial. There are multiple variants of H. rosa-sinensis which confers different levels of antimicrobial, antioxidant and wound healing activity as each variant consists of different levels of phytochemicals. Thus, accurate identification is critical so that each of their medicinal properties can be utilized to the fullest degree. However, the variants only differ in flower colours and shapes but are similar looking shrubs. The flowers of the H. rosa-sinensis are not present all the time and are short lived, leading to the difficulty in accurately identifying each variant based solely on morphology. Thus, DNA barcoding is a possible complement to traditional morphology based identification and discrimination. In this study, the combination of trnH-psbA and matK sequences were used as barcodes to discriminate three different variants of H. rosasinensis. The variants that were sequenced under this study are provisionally identified as H. rosa-sinensis Fijian white, H. rosa-sinensis with a single layer of pink petals and H. rosa-sinensis with a single layer of orange petals. DNA extraction using a modified Edward’s method, amplification and sequencing were successful, with good quality sequences being generated in most cases. The probability that these sequences were not pseudogenes or contaminants were verified using BLAST and DOGMA. The phylogenetic tree generated showed that the trnH-psbA marker has higher discriminatory power than the matK marker due to its ability to assess intraspecific relationship of the variants with high confidence. As there are few studies that had been done on DNA barcoding of H. rosasinensis variants, the DNA sequences of this current research will contribute to the public